2022
DOI: 10.1186/s42269-022-00786-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular binding studies of anthocyanins with multiple antiviral activities against SARS-CoV-2

Abstract: Background The search for ideal drugs with absolute antiviral activity against SARS-CoV-2 is still in place, and attention has been recently drawn to natural products. Several molecular targets have been identified as points of therapeutic intervention. The targets used in this study include SARS-CoV-2 helicase, spike protein, RNA-dependent RNA polymerase, main protease, and human ACE-2. An integrative computer-aided approach, which includes molecular docking, pharmacophore modeling, and pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Herbals known to be rich in polyphenolics, e.g ., anthocyanins, catechins, and ellagitannins, among others were primarily focused on selecting the candidate components of the formulation. A reference survey has revealed that green tea extract ( Tallei et al, 2021 ), bilberry extract ( Akinnusi, Olubode, & Salaudeen, 2022 ), and dried pomegranate peel extract (Suručić et al, 2021a) as well as propolis extract ( Salatino, 2022 ) have been proposed as the active extracts against SARS-CoV-2, based on the in vitro and in silico experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbals known to be rich in polyphenolics, e.g ., anthocyanins, catechins, and ellagitannins, among others were primarily focused on selecting the candidate components of the formulation. A reference survey has revealed that green tea extract ( Tallei et al, 2021 ), bilberry extract ( Akinnusi, Olubode, & Salaudeen, 2022 ), and dried pomegranate peel extract (Suručić et al, 2021a) as well as propolis extract ( Salatino, 2022 ) have been proposed as the active extracts against SARS-CoV-2, based on the in vitro and in silico experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Wuhan and Omicron, two known dominant variants, were investigated in the present study to observe the efficiency of the chewable tablet would alter in response to the virus's mutations. When searching the existing literature on the antiviral activity of the components in the chewable tablet against SARS-CoV-2, the results were mainly conducted using in-silico , molecular docking studies ( Akinnusi et al, 2022 , Vardhan and Sahoo, 2020 , Guler et al, 2021 ) rather than experiments performed with live virus under BSL-3 conditions. Since such data cannot always accurately represent the present situation, verification is always necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A library of 118 anthocyanins was obtained from phytohub database in SMILES format and converted to 2D (sdf) format using Marvin sketch. 23 The compounds were incorporated into Maestro (2017 release) and subsequently prepared using the Ligprep functional tool. Similarly, the 3D structures of the protein targets (depiptidyl peptidase IV PDB ID: 3VJM, pancreatic alpha-amylase PDB ID: 4GQR, and PTP1B PDB ID: 1KAV) were obtained from an online repository (rcsb.org).…”
Section: Methodsmentioning
confidence: 99%
“…Anthocyanins have been found to have antiviral, anti-inflammatory, and antioxidant properties, which may be beneficial in preventing the spread of the virus. Studies have shown that anthocyanins can bind to the virus' surface proteins and disrupt its ability to enter and infect host cells [29]. Additionally, it was found that anthocyanins could inhibit the nuclear factor-κB (NF-κB) pathway by regulating the miR-138-5p/sirtuin-1 (SIRT1) axis, thus inhibiting airway inflammation in asthmatic mice [30].…”
Section: Antioxidants In Attenuating Covid-19 Symptomsmentioning
confidence: 99%